Book Review: Experimentelle Archäologie in Europa, Jahrbuch 2018 - Stefanie Ulrich (EXARC Journal)
Like the previous issues, this periodical (Jahrbuch) is published by Gunter Schöbel and the European Association for the advancement of archaeology by experiment e. V. (Europäische Vereinigung zur Förderung der Experimentellen Archäologie) in collaboration with the Pfahlbaummuseum Unteruhldingen. It is the 17th issue of the periodical and includes 21 essays on 250 pages, presenting the contributions of the EXAR conference from 28th September to 1st October 2017 as well as the annual report (Jahresbericht, p. 245) and the instructions for authors (Autorenrichtlinien, p. 249) of Experimentelle Archäologie in Europa.